Coupled dipole plasmonics of nanoantennas in discontinuous, complex dielectric environments. (November 2015) - Forcherio, Gregory T.; Blake, Phillip; Seeram, Manoj; DeJarnette, Drew; Roper, D. Keith
Abstract: Two-dimensional metamaterials support both plasmonic and coupled lattice (Fano) resonant modes that together could enhance optoelectronics. Descriptions for plasmon excitation in Fano resonant lattices in non-vacuum environments typically use idealized, homogeneous matrices due to computational expense and limitations of common approaches. This work described both localized and coupled resonance activity of two-dimensional, square lattices of gold (Au) nanospheres (NS) in discontinuous, complex dielectric media using compact synthesis of discrete and coupled dipole approximations. This multi-scale approach supported attribution of experimentally observed spectral resonance energy and bandwidth to interactions between metal and dielectric substrate(s) supporting the lattices. Effective polarizabilities of single AuNS, either in vacuo or supported by glass and/or indium tin oxide (ITO) substrates, were obtained with discrete dipole approximation (DDA). This showed plasmon energy transport varied with type of substrate: glass increased scattering, while ITO increased absorption and energy confinement. Far-field lattice interactions between AuNS with/without substrates were computed by coupled dipole approximation (CDA) using effective polarizabilities. This showed glass enhanced diffractive features (e.g., coupled lattice resonance), while ITO supported plasmon modes. This compact, multiscale approach to describe metasurfaces in complex environments could accelerate their development and application. Highlights: Coupled and discrete dipole approximate computation of gold metasurfaces. Fano resonant nanoantenna lattices in complex dielectric environments. Experimental transmission UV–vis spectra decomposition elucidated substrate effects. ITO affected surface plasmon resonance and glass affected diffractive features.